2009
DOI: 10.1371/journal.pone.0007849
|View full text |Cite
|
Sign up to set email alerts
|

Impact of RTS,S/AS02A and RTS,S/AS01B on Genotypes of P. falciparum in Adults Participating in a Malaria Vaccine Clinical Trial

Abstract: ObjectiveRTS,S, a candidate vaccine for malaria, is a recombinant protein expressed in yeast containing part of the circumsporozoite protein (CSP) sequence of 3D7 strain of Plasmodium falciparum linked to the hepatitis B surface antigen in a hybrid protein. The RTS,S antigen is formulated with GSK Biologicals' proprietary Adjuvant Systems AS02A or AS01B. A recent trial of the RTS,S/AS02A and RTS,S/AS01B vaccines evaluated safety, immunogenicity and impact on the development of parasitemia of the two formulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 30 publications
4
56
1
1
Order By: Relevance
“…‫,ء‬ P Ͻ 0.001 versus the nonimmune (N) group as determined by the Wilcoxon-Mann-Whitney test; ‫,ءء‬ P Ͻ 0.001 between the S and L groups as determined by the Wilcoxon-Mann-Whitney test; ‫,ءءء‬ P Ͻ 0.001 among the three groups (S, M, and L) as determined by the KruskalWallis test; †, P Ͻ 0.005 versus the nonimmune (N) group as determined by the chi-square test; † †, P Ͻ 0.005 between the indicated two groups as determined by the chi-square test. (20,29), and the GlaxoSmithKline adjuvant systems (GlaxoSmithKline, Brentford, United Kingdom) (8,27), will expedite malaria vaccine development. It is also possible that protein delivery molecules will ultimately be combined with effective oil or other adjuvants, including aluminum hydroxide.…”
Section: Discussionmentioning
confidence: 99%
“…‫,ء‬ P Ͻ 0.001 versus the nonimmune (N) group as determined by the Wilcoxon-Mann-Whitney test; ‫,ءء‬ P Ͻ 0.001 between the S and L groups as determined by the Wilcoxon-Mann-Whitney test; ‫,ءءء‬ P Ͻ 0.001 among the three groups (S, M, and L) as determined by the KruskalWallis test; †, P Ͻ 0.005 versus the nonimmune (N) group as determined by the chi-square test; † †, P Ͻ 0.005 between the indicated two groups as determined by the chi-square test. (20,29), and the GlaxoSmithKline adjuvant systems (GlaxoSmithKline, Brentford, United Kingdom) (8,27), will expedite malaria vaccine development. It is also possible that protein delivery molecules will ultimately be combined with effective oil or other adjuvants, including aluminum hydroxide.…”
Section: Discussionmentioning
confidence: 99%
“…Because CSP is polymorphic, an obvious question was whether diversity in CSP may explain the partial efficacy of the RTS,S vaccine. Analyses of infecting genotypes in one phase II trial of RTS,S suggested that this was not the case as there was no evidence of selection for infections containing non-vaccine genotypes among vaccinated versus control subjects [197,198]. These findings highlight that although antigen polymorphism needs to be considered in vaccine development, it may not be a major issue for all vaccines.…”
Section: Vaccine Trials and Antigen Polymorphismmentioning
confidence: 98%
“…43 RTS contains three distinct portions, the first of which is a single polypeptide chain that corresponds to a large region of the highly conserved tandem repeat (R) tetra-peptide sequence from CSP; each repeat tetra-peptide is called NANP. 44,45 There are 19 copies of NANP and it is named for its amino acid sequence.…”
Section: Molecular Structurementioning
confidence: 99%
“…42,44 The 'R' and 'T' components correspond to amino acids 207-395 on CSP of the 3D7 standard laboratory strain of P. falciparum. 42,44,45 Fig. 3 shows a simplified representation of the 'RT' peptide chain.…”
Section: Molecular Structurementioning
confidence: 99%